Gait Speed Decrease in pre-frail and frail elderly with Type 2 Diabetes Mellitus and associated factors - Patrício, Íkaro Felipe da Silva (2019)
Walking Speed Decreasing (WSD) is an important data in the functional performance of the elderly and is a clinical condition found in frailty and type 2 Diabetes Mellitus (DM2). The objective is to determine the sociodemographic and clinical-functional factors related to WSD in pre-frail and frail diabetic elderly. Age group, falls in the last year and risk of falls are the variables that are most closely related. Furthermore, age, polypharmacy and the risk of falls obtained a greater difference between the groups.